High temperature wear and corrosion behavior of detonation sprayed Fe-based amorphous coatings - Lu Xie; Yueming Wang (Scientific Reports)
Abstract FeCrMoCB amorphous coatings were prepared by detonation spraying technology. The coating microstructure, elements distribution, microhardness distribution, wear behaviors under various temperatures and the electrochemical corrosion resistance were discussed, respectively. It was found the amorphous content of the detonation sprayed Fe-based amorphous coating can reach 84.6%, higher than the other usual thermal spray technologies. The coating microhardness reached 900 HV0.5, and the wear rate of the amorphous coating was about 47 × 10− 6 mm3/N.m. The coating under 400 °C exhibited the strongest wear resistance among the coatings under various temperatures due to the oxidation appeared during the fabrication process, and several big cracks appeared in the coating under 600 °C because of the coating brittleness.